Ecological assessment of heavy metals in soil around a coal-fired thermal power plant in Turkey - Turhan, Ş.; Garad, A. M. K.; Hançerlioğulları, A.; Kurnaz, A.; Gören, E.; Duran, C.; Karataşlı, M.; Altıkulaç, A.; Savacı, G.; Aydın, A. (Springer Science and Business Media LLC, 2020)
In this study, heavy metal concentrations in agricultural surface soil (0–5 cm) samples collected from the area around the Kangal lignite-fired thermal power plant were determined using energy-dispersive X-ray fluorescence spectrometry. Also, the pH values of agricultural soil samples were measured to assess the level of acidification. Geo-accumulation index (Igeo), enrichment factor (EF), contamination factor (CF), contamination degree (CD), modified contamination degree (mCD), and pollution load index (IPL) were estimated to assess the heavy metals pollution in soil samples. The average concentration of Fe, Ti, Mn, Cr, Ni, Zn, Zr, Co, Cu, Pb, As, Sn and Hg was found as 39,065 ± 5096, 2262 ± 738, 721 ± 119, 713 ± 236, 610 ± 199, 82 ± 37, 65 ± 26, 64 ± 19, 29 ± 3, 17 ± 7, 9 ± 7, 3 ± 1 and 2 ± 1 mg kg−1, respectively. The values of pH varied from 7.5 to 8.2 with an average value of 8.0 (moderately alkaline). The Igeo, EF and CF results reveal that the study area is heavily or very highly contaminated with Cr, Ni, and Hg. On the basis of the IPL value, the soil samples are polluted with heavy metals. However, the mCD indicates moderate heavy-metal contamination of the soil samples.
Keywords: Lignite-fired power plant; Soil pollution; Geo-accumulation index; Geo-Accumulation Index; Contamination factor; Pollution Load Index; Heavy Metals; Enrichment factor; Enrichment Factor; Heavy metals; Contamination Factor; Lignite-Fired Power Plant; Pollution load index; Soil Pollution; 2. Zero hunger; 7. Clean energy; 6. Clean water; 13. Climate action